2020
DOI: 10.1021/acs.jpcb.0c04272
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Arresting an Unusual Amide Tautomer Using Divalent Cations”

Abstract: Metrics & MoreArticle Recommendations * sı Supporting InformationH erein, we comment on the of spectroscopic data in "Arresting an Unusual Amide Tautomer Using Divalent Cations", J. Phys. Chem. B 2019, 123 (40), 8419−8424, by Bagchi and co-workers. 1 In their paper, the authors assign the appearance of a blue-shifted shoulder on the amide I vibration of N-methylacetamide (NMA), N,Ndimethylacetamide (DMA), and urea to the formation of a tautomer-like structure in the presence of divalent metal cations. In other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Previous studies have, however, shown that the introduction of certain cations can lead to a new resonance that shows up as a blue shoulder approximately 20–25 cm –1 above the frequency of the main carbonyl resonance (i.e., in the case of amides). ,, This happens when the cation contact pairs with the CO oxygen atom and dehydrates it (Figure S2). As such, CO···H 2 O hydrogen bonds are displaced . By contrast, the continuous Stark shift in the hydrated bond resonance toward lower frequencies should arise from water-separated ions that act via a through space electric field.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have, however, shown that the introduction of certain cations can lead to a new resonance that shows up as a blue shoulder approximately 20–25 cm –1 above the frequency of the main carbonyl resonance (i.e., in the case of amides). ,, This happens when the cation contact pairs with the CO oxygen atom and dehydrates it (Figure S2). As such, CO···H 2 O hydrogen bonds are displaced . By contrast, the continuous Stark shift in the hydrated bond resonance toward lower frequencies should arise from water-separated ions that act via a through space electric field.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have, however, shown that the introduction of certain cations can lead to a new resonance that shows up as a blue shoulder approximately 20−25 cm −1 above the frequency of the main carbonyl resonance (i.e., in the case of amides). 47,49,56 This happens when the cation contact pairs with the CO oxygen atom and dehydrates it (Figure S2). 56 As such, CO••• H 2 O hydrogen bonds are displaced.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations